2022
DOI: 10.1126/sciimmunol.abm1803
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium septicum α-toxin activates the NLRP3 inflammasome by engaging GPI-anchored proteins

Abstract: Clostridium species are a group of Gram-positive bacteria that cause diseases in humans, such as food poisoning, botulism, and tetanus. Here, we analyzed 10 different Clostridium species and identified that Clostridium septicum , a pathogen that causes sepsis and gas gangrene, activates the mammalian cytosolic inflammasome complex in mice and humans. Mechanistically, we demonstrate that α-toxin secreted by C. septicum binds to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…The majority of bacterial toxins that activate the NLRP3 inflammasome are pore‐forming toxins; however, several enzymatic toxins which do not induce pore‐formation, such as Mycoplasma pneumoniae CARDS toxin and Shiga toxin, have been reported to activate the NLRP3 inflammasome (Bose et al , 2014 ; Lee et al , 2016 ). Unlike pore‐forming toxins that emanate a signal from the plasma membrane to trigger K + efflux and subsequent NLRP3 activation (Jing et al , 2022 ), lecithinase accesses the lysosome to trigger NLRP3 activation. Several exogenous activators of NLRP3, such as asbestos and silica crystals (Dostert et al , 2008 ; Hornung et al , 2008 ), and endogenous aggregates, including circulating ASC specks, neuronal amyloid‐β fibrils and multiple myeloma‐associated β 2 ‐microglobulin fibrils (Halle et al , 2008 ; Franklin et al , 2014 ; Hofbauer et al , 2021 ), have been described to undergo a pathway of internalization, endo‐lysosomal trafficking and lysosomal membrane destabilization.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of bacterial toxins that activate the NLRP3 inflammasome are pore‐forming toxins; however, several enzymatic toxins which do not induce pore‐formation, such as Mycoplasma pneumoniae CARDS toxin and Shiga toxin, have been reported to activate the NLRP3 inflammasome (Bose et al , 2014 ; Lee et al , 2016 ). Unlike pore‐forming toxins that emanate a signal from the plasma membrane to trigger K + efflux and subsequent NLRP3 activation (Jing et al , 2022 ), lecithinase accesses the lysosome to trigger NLRP3 activation. Several exogenous activators of NLRP3, such as asbestos and silica crystals (Dostert et al , 2008 ; Hornung et al , 2008 ), and endogenous aggregates, including circulating ASC specks, neuronal amyloid‐β fibrils and multiple myeloma‐associated β 2 ‐microglobulin fibrils (Halle et al , 2008 ; Franklin et al , 2014 ; Hofbauer et al , 2021 ), have been described to undergo a pathway of internalization, endo‐lysosomal trafficking and lysosomal membrane destabilization.…”
Section: Discussionmentioning
confidence: 99%
“… 3 Targeting various inflammasome subunits including ASC and NLRP3 through inhibitors or depletion can effectively abolish pyroptosis. 32 , 33 Our initial hypothesis was that DHA initiated ovarian cancer cell pyroptosis in a similar manner. Quite in the contrary, we found that depletion of ASC or inhibiting NLRP3 with MCC950 exhibited little effect on DHA-induced caspase-1 activation and cell death, indicating that DHA-led caspase-1 activation and pyroptosis occur in a mechanism not involving in ASC or NLRP3.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that NLRP3 inflammasome assembly and activation lead to the secretion of proinflammatory cytokines, including IL-1β and IL-18. It has been reported that NLRP3 is activated by different pathogens, such as Mycobacterium tuberculosis (M.tb) [ 8 ], Staphylococcus aureus [ 9 ], and Clostridium septicum [ 10 ], and NLRP3 plays an important role in protecting the host against infection. Similarly, our previous study showed that P. multocida activates the NLRP3 inflammasome, leading to caspase-1 activation and subsequent IL-1β secretion in vivo and in vitro, and this NLRP3 inflammasome activation depends on macrophage phagocytosis [ 11 ].…”
Section: Introductionmentioning
confidence: 99%